Research on synchronous load control of shield beam for 50,000 kN hydraulic support test bench - Chengfeng Wu; Tiangu Wu; Lijuan Zhao; Wenliang Li; Qingliang Zhang; Lin Li; Qing Chen (PLoS ONE, 2025)
This paper proposes an innovative synchronous load control system for protective beams, addressing the issues of uneven loading and asynchronous positioning in dual-cylinder loading systems during hydraulic support shield beam loading experiments. The system integrates multi-domain modeling and co-simulation technologies using tools such as Simulink, AMESim, and Adams, creating a unified model encompassing mechanical, hydraulic, and control aspects. This approach enables precise perception, signal processing, and adaptive regulation of the dynamic loading process.The core of this research lies in the application of an adaptive RBF-PID control strategy, benchmarked against a fuzzy PID controller. Simulation results demonstrate that the RBF-PID controller exhibits significant advantages in handling uneven loads and achieving rapid resynchronization, with a 61% reduction in maximum synchronization error and a 34% improvement in resynchronization speed compared to the fuzzy PID control. Concurrently, stress analysis identified the pinhole connection position as the area with the most concentrated stress on the protective beam loading block, providing critical data support for structural strength design.Finally, experimental verification conducted on a 50000kN hydraulic support test bench validates the effectiveness and feasibility of this control strategy in real-world conditions. The experimental results are highly consistent with simulation outcomes, effectively resolving engineering challenges encountered during the protective beam loading process and offering new insights and methods for the optimization and control strategy development of hydraulic support test benches.